Surface energy anisotropy for the low-index crystal surfaces of the textured polycrystalline BCC tungsten: experimental and theoretical analysis - Belyaeva, A.I.; Savchenko, A.A.; Galuza, A.A.; Kolenov, I.V. (Вопросы атомной науки и техники, 2017)
Summarizing the experimental and theoretical trends observed on the changes in surface microstructure and topography resulting from surface energy anisotropy for the low-index crystal surfaces of the polycrystalline bcc tungsten under sputtering is done. A brief summary of the most closely related work is included. The experimental results have been discussed in the framework of the various theoretical methods. Emphasis was placed on the problems which are existing up to now. It is shown that the absence of a common trend in the ordering of the (100), (110), and (111) surface energies amongst the various theoretical models is a problem yet to be satisfactorily discussed. It is shown experimentally that for polycrystalline textured tungsten (bcc metal), the order of the three low-index surface energies is γ(111) > γ(100) > γ(110).